THE USE OF WEBSITE-BASED LEARNING MEDIA TO IMPROVE THE READING SKILLS OF MADRASAH TSANAWIYAH STUDENTS - Adam Mudinillah; Sri Nur Rahmi; Fitria Hanifah; Vugar Abdullayev (Yayasan Adra Karima Hubbi, 2026)
Advances in technology and communication tools in education have developed rapidly and become increasingly sophisticated, so paper-based learning has increasingly been set aside in education. One example is the use of online learning through the development of a learning-media website using Google Sites that contains games, quizzes, engaging and innovative videos, and other features to support students’ success. This study aimed to create a learning-media website using Google Sites for reading skills. The study employed a quantitative method, and data were obtained from online interviews and online questionnaire distribution. The questionnaire was distributed to Madrasah Tsanawiyah students online by using Google Forms. The findings showed that the use of educational websites in the Education 5.0 era could benefit students, as demonstrated by improvements in various aspects of the four language skills. It can be concluded that the use of an appropriate website as a learning medium was attractive and innovative, as indicated by the finding that 80% of students obtained the highest scores. This study was limited because the research was conducted only online and not directly in the field. The researchers expect future researchers to examine other learning media. This study also recommends that future researchers use it as an additional reference when conducting research on language-learning websites.